PENTINGNYA PENDIDIKAN KEWARGANEGARAAN DALAM MENGATASI KRISIS KONSITUSI DI INDONESIA: PELAJARAN DARI KASUS SEJARAH - Lestari, Egitia Dwi; Putri, Desi Aulia; Prawinata, Hendru (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2024)
Civic education has an important role in overcoming the constitutional crisis in Indonesia. Through civic education, people can think critically, creatively, and responsibly. In addition, the public can also have a greater ability to actively participate in the political process and hold the government accountable, and can reduce the likelihood of a constitutional crisis in the future. The constitutional crisis is a phenomenon that can shake the political and social stability of a country. Citizenship plays an important role as a key element that helps maintain the integrity and resilience of the country's constitution. In Indonesia, which has a long history of facing various constitutional crises, the role of citizenship is often a key factor in overcoming these challenges. This study explores the role of citizenship in overcoming the constitutional crisis in Indonesia through the analysis of several important historical cases. This study uses a systematic review method. The data collection method is carried out through documentation and literature studies. The data analysis technique uses source triangulation, which is in the form of searching for data from various sources of different journals and libraries to ensure data suitability. The results of the study show that effective civic education can increase political awareness and participation, reduce legal uncertainty, and strengthen trust in democratic institutions. Through this analysis of historical cases, it is evident that countries that consistently implement civic education are better able to face constitutional challenges.